Immune Responses to RHAMM in Patients with Acute Myeloid Leukemia after Chemotherapy and Allogeneic Stem Cell Transplantation - Casalegno Garduño, Rosaely; Schmitt, Anita; Schmitt, Michael (Clinical & developmental immunology, 2012)
Leukemic blasts overexpress immunogenic antigens, so-called leukemia-associated antigens like the receptor for hyaluronan acid-mediated motility (RHAMM). Persistent RHAMM expression and decreasing CD8